2013
DOI: 10.5897/ajps13.100
|View full text |Cite
|
Sign up to set email alerts
|

In vitro propagation of Anchote (Coccinia abyssinica) (Lam.) Cogn.]

Abstract: Coccinia abyssinica (Lam.) Cogn.] (Cucurbitaceae) is a tuberous neutraceutical plant locally known as Anchote (Oromo language). A micropropagation protocol was developed for C. abyssinica. Seeds were planted ex vitro in a pot that contained different soil mix ratios, and two weeks old seedlings were used as a source of explants. Shoot tip and nodal explants were sterilized and cultured on full MS medium variously supplemented with 6-benzylaminopurine (BAP), indole acetic acid (IAA), naphthaleneacetic acid (NAA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
1
9
1
Order By: Relevance
“…During the current study, nodal explants cultured on media supplemented with 2.5 mM kinetin produced 72% frequency of shoot multiplication. This is contrary to the work of Bekele et al (2013), who reported very low (23%, 27%, and 44%) frequency of microshoot induction when 1, 2, and 3 mM kinetin was used, respectively.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…During the current study, nodal explants cultured on media supplemented with 2.5 mM kinetin produced 72% frequency of shoot multiplication. This is contrary to the work of Bekele et al (2013), who reported very low (23%, 27%, and 44%) frequency of microshoot induction when 1, 2, and 3 mM kinetin was used, respectively.…”
Section: Discussioncontrasting
confidence: 98%
“…Explant contamination is a function of several plant and environmental related factors such as plant species, age, explant source, and prevailing weather condition. Previous workers on anchote used explants from in vitro-germinated seedlings (which did not require sterilization) and nodal explants derived from seedling growing in the greenhouse (Bekele et al, 2013;Yambo and Feyissa, 2013). During the current study, a higher percent number of clean explants were obtained than the numbers reported by Yambo and Feyissa (2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is traditionally recommended to feed women that give birth due to the fact that it contains high Ca and Fe [8]. It can also be used to treat gonorrhea, tuberculosis and tumor cancer due to active ingredient contents [11,17,19]. Therefore, anchote is one of the food crops that help to maintain health of the consumers in addition to its nutritional value.…”
Section: Benefits Of Anchotementioning
confidence: 99%
“…Plant micropropagation reports in Ethiopia should thus pay attention to these presumed controversies and contribute their share to address some of the existing controversies in order to expand the application of micropropagation with the desired repeatability and standards. Diverse plant species including cereals, oil crops, spices, medicinal plants, high-value crops, fruit plants, root crops, and endangered multipurpose shrubs were utilized in various forms of plant micropropagation in Ethiopia [10][11][12][13][14][15][16][17][18][19][20], [21][22][23][24][25][26][27][28][29][30][31], [32][33][34][35][36][37][38][39][40][41][42], [43][44][45][46][47][48][49][50][51][52][53][54][55]. Critical assessment of these studies would facilitate the development of repeata...…”
Section: Introductionmentioning
confidence: 99%